Regulatory Cost of Capital of the Brazilian Electricity Distribution Companies: A Proposed Modeling by Time Series - Silva, Lucas Machado Coelho; Correia, Laise Ferraz; Amaral, Hudson Fernandes; Raad, Lucélia Viviane Vaz (Advances in Scientific and Applied Accounting, 2025)
Objective: The aim of this paper was to propose the use of time series models to forecast long series components of the regulatory WACC of the Brazilian electricity distributors, instead of the mean or median used by ANEEL. Method: To calculate the regulatory WACC components in the first five CRTPs and the proposed WACC, we used the same database employed by ANEEL, available on its website. ARMA and AR models were used to estimate the long series components USTB, S&P500, EMBI+, and CPI, find the proposed WACC, and subsequently compare it with the ANEEL WACC in the first five CRTPs. Results: The estimates from time series models were different from those calculated by ANEEL for the components in the first five CRTPs. Thus, the regulatory WACC was reduced in some CRTPs and increased in others. On average, the values obtained in this study are lower than those of ANEEL, but the differences are very small. The components estimated by time series models, as well as the WACC, oscillated more along the five CRTPs compared to those of ANEEL. Contributions: This paper’s contribution was broadening the discussion on the methods of supporting the investment decisions of regulated companies. We consider the models proposed more appropriate because the series of the regulatory WACC components may be non-stationary and have an autocorrelation structure. In that case, their means or medians would not be appropriate estimates of future values.